2019
DOI: 10.11114/afa.v6i1.4650
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Financial Risk Management Practices on Financial Performance: Evidence from Commercial Banks in Botswana

Abstract: The study examined the impact of financial risk management practices on the financial performance of commercial banks in Botswana. The study used Return on Asset and Return on Equity to measure financial performance. Inflation, Interest rates, total debt to total assets, total debt to total equity, total equity to total assets and loan deposit ratios were used as proxies for financial risk management. The research population was all the 10 commercial banks in Botswana and the study covered a period of 8 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In addition, Lotto (2019) pointed out that the capital adequacy ratio has a positive correlation with the operational efficiency of banks, and reduces the risk of moral hazard between shareholders and debt-holders. Similarly, the research of Kiambati (2020) and Sathyamoorthi et al (2020) demonstrated that there is a relationship between risk management and profitability or shareholder market value among the commercial banks. Furthermore, Jiang and Feng (2020) emphasize the importance of risk management capabilities which is hardly observable but contributes much to firm value.…”
Section: The Risk Management and Bank Performancementioning
confidence: 95%
See 1 more Smart Citation
“…In addition, Lotto (2019) pointed out that the capital adequacy ratio has a positive correlation with the operational efficiency of banks, and reduces the risk of moral hazard between shareholders and debt-holders. Similarly, the research of Kiambati (2020) and Sathyamoorthi et al (2020) demonstrated that there is a relationship between risk management and profitability or shareholder market value among the commercial banks. Furthermore, Jiang and Feng (2020) emphasize the importance of risk management capabilities which is hardly observable but contributes much to firm value.…”
Section: The Risk Management and Bank Performancementioning
confidence: 95%
“…This idea is in conformity with Brown et al (2009) and Zgarni (2018) line of thought, confirming that risk management stands as an important undertaking for banks to create value. Similarly, the research of Lotto (2019), Kiambati (2020) and Sathyamoorthi et al (2020) demonstrated that there is a relationship between risk management and profitability or shareholder market value among the commercial banks.…”
Section: Sourcementioning
confidence: 95%
“…In contrast, a negative and significant relationship was obtained between liquidity (among other variables) with bank profitability in Botswana for a period from 2004 to 2013, using ordinary least square technique (Seemule, Sinha and Ndlovu, 2017). Other studies in Botswana context which assessed the impact of liquidity (among other independent variables) on bank performance and yielded conflicting results include, among others: (Sathyamoorthi, Mapharing, Mphoeng, & Dzimiri, 2019;Mbekomize & Mapharing, 2017;Ndlovu, 2015;Amusa & Kayawe, 2003).…”
Section: Background Informationmentioning
confidence: 99%
“…The findings provide evidence that the assertion made by Fatemi and Fooladi (2006), Hosna et al (2009), Toutou and Xiaodong (2011), Zeze (2012), Trofimov et al (2018) and Zgarni and Hassouna (2018) sets out that risk management improves the bank performance. Similarly, the research of Kiambati (2020) and Sathyamoorthi et al (2020) demonstrated that there is a relationship between credit risk and shareholder market value among the commercial banks.…”
Section: Resultsmentioning
confidence: 91%
“…Findings of Kiambati (2020) and Sathyamoorthi, Mogotsinyana, Mphoeng and Mashoko (2020) suggest that commercial banks should strike a proper balance between financial risk management practices and financial performance by engaging in appropriate market, credit, and liquidity risk management practices that will ensure safety for their banks and yield positive profits. Consequently, we present the following hypothesis:…”
Section: Risk Management and Bank Performancementioning
confidence: 99%